MEKANISME KOPING PASIEN GAGAL GINJAL KRONIK DALAM MENJALANKAN HEMODIALISIS: LITERATURE REVIEW - Nurhayati, Risa; Wahyuni, Sri; Bayhakki, Bayhakki (Poltekkes Kemenkes Bandung, 2024)
Chronic kidney disease (CKD) has been identified as a serious public health issue. Patients with end-stage renal disease undergoing hemodialysis (HD) report a significant decline in life satisfaction, particularly due to physical fatigue, social limitations, and psychosocial problems. According to the Centers for Disease Control and Prevention (CDC) in 2021, CKD progresses slowly and affects more than 10% of the global population, equivalent to approximately 800 million individuals. This literature review aims to explore the coping experiences of patients undergoing hemodialysis. The sample criteria for articles were based on PICOS elements, specifically focusing on the coping mechanisms of hemodialysis patients. The databases used include PubMed, Science Direct, and Google Scholar, with keywords targeting the coping mechanisms of patients undergoing hemodialysis. A total of seven articles were retrieved. The search results underwent a screening process using PICO elements (Population/Patient/Problem, Intervention, Comparison, Outcome) and the CRAAP method (Currency, Relevance, Authority, Accuracy, Purpose), with inclusion criteria limited to adult patients. The findings identified eight main themes: physical activity, satisfaction with physical fitness during hemodialysis, perceptions of their condition during hemodialysis, sleep quality during therapy, personal adaptation to physical changes, social relationships, changes in economic status during therapy, and spiritual responses. In conclusion, spiritual and medical approaches, along with biological, psychological, social, and spiritual impacts, play crucial roles in shaping patients’ experiences. A deeper understanding of these themes can assist healthcare providers in designing more effective and holistic interventions to improve the quality of life for CKD patients undergoing hemodialysis.